Wind turbine control: open-source software for control education, standardization and compilation. (January 2020) - Mulders, S P; Zaaijer, M B; Bos, R; van Wingerden, J W
Abstract: Standardized, easy to use, and preferably open-source research software is an important aspect in supporting and solidifying the wind turbine community. To this end, three contributions in the form of open-source software projects are presented in this paper. First, a community-driven wind turbine baseline controller, the Delft Research Controller (DRC), is presented. The DRC is applicable to high-fidelity simulation software that uses the DISCON controller interface. The controller distinguishes itself by the variety of available control and estimation implementations, its ease of use, and the universal applicability to wind turbine models. Secondly, in the wake of the DRC, the SimulinkDRC graphical controller design and compilation environment has been developed. Users having access to Simulink can benefit from the convenient way of controller development the tool provides. Finally, the FASTTool has been developed for educational purposes, by focusing on the graphical aspect of wind turbine (controller) design. The tool simplifies interaction with the advanced FAST simulation software, by comprehensive visualizations and analysis tools. This paper demonstrates and describes the functionality of all three software projects.